(untitled) (Educação e Pesquisa, 2021)
This article discusses the contributions of American philosopher and activist Nancy Fraser to the debate on redistribution and recognition, analyzing possible repercussions on the relationship between justice and education. The debate presented here has been one of the most fruitful in the social sciences in recent years, with strong impact on social and educational policies. It is all about understanding to what extent policies prioritize more universal aspects, focusing on the concept of equity and its consequences, or actions to recognize identities, an agenda that has gained centrality, including educational discourses stemming from the debate on gender. Known for her role in the debate on feminism, in her analyses Fraser has focused on the organization of discourses and political actions in the context of national and transnational struggles. Based on Fraser’s contributions, we seek to understand the tensions of this debate and the conciliatory perspectives between the two strands. Eventually, we seek to reflect on how redistribution and recognition influence the educational debate, especially in the contemporary social and political context. With a conciliatory tendency, Fraser points the possibility of bridges between politcal actions that enhance the identities of subjects and those that strengthen historical struggles linked to the universalization of rights and fair financial distributions that, in countries like Brazil, are still far from being themes of a distant past.